Isolated Humeral Metastasis in Uterine Cervical Cancer: A Rare Entity - Malek, Mahrooz; Kanafi, Alireza Rajabzadeh; Pourghorban, Ramin; Nafisi-Moghadam, Reza
Bone metastasis in cancer of uterine cervix, especially in the form of isolated bone involvement is a rare manifestation. Herein, we report the first case of isolated humeral metastasis in a known case of locally advanced cervical cancer. A fifty-six-year old female presented with International Federation of Gynecology and Obstetrics (FIGO) Stage IV A squamous cell carcinoma of uterine cervix. She was treated with a combination of radiation and chemotherapy and then total abdominal hysterectomy with bilateral salpingo-oophorectomy. Seven months later, she developed an isolated lytic lesion in the left humerus, which turned out to be a bone metastatic lesion.